Privacy risk adaptive access control model via evolutionary game - Hongfa DING; Changgen PENG; Youliang TIAN; Shuwen XIANG (Tongxin xuebao)
Aiming at the problem that in the private sensitive date centralized and opening information systems,a fine-grained and self-adaptive access control model for privacy preserving is desperately needed,thus the balance between privacy preserving and data access utility should be achieved,a rational multi-player risk-adaptive based access control model for privacy preserving was proposed.Firstly,the privacy risk values of access request and requester were formulized by the private information quantity of the requested dataset,and by using Shannon information.Secondly,a risk-adaptive based access control evolutionary game model was constructed by using evolutionary game under the supposing of bounded rational players.Furthermore,dynamic strategies of participants were analyzed by using replicator dynamics equation,and the method of choosing evolutionary stable strategy was proposed.Simulation and comparison results show that,the proposed model is effective to dynamically and adaptively preserve privacy and more risk adaptive,and dynamic evolutionary access strategies of the bounded rational participants are more suitable for practical scenarios.